Rainwater Harvesting Capacity Assessment for Domestic Water Supply at Wreda Griya Nugraha Nursing Home - Aprizal; Rani Anggita Hutagalung; Kaka Pahingga; Ni Luh Chanda Swandewi; Feny Nilam Cahya (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Rainwater harvesting has become an increasingly important alternative for improving water security and reducing dependence on groundwater, particularly in urban areas vulnerable to seasonal water shortages. This study evaluates the potential of a rainwater harvesting system to satisfy domestic water demand at Wreda Griya Nugraha Nursing Home, Bandar Lampung, Indonesia. Daily rainfall records from four rainfall stations covering the period 2009–2023 were analyzed using the Arithmetic Mean, Thiessen Polygon, and Isohyetal methods to estimate areal rainfall. Runoff volumes generated from the building roof were calculated and incorporated into a water balance simulation considering storage inflow, domestic water demand, and storage outflow under several supply scenarios. The simulation indicates that a roof catchment area of 1,627.92 m² combined with a 15 m³ storage tank provides the most effective configuration for rainwater utilization. The proposed system is capable of supplying approximately 60% of the annual domestic water demand, equivalent to meeting water requirements for more than ten months each year under average rainfall conditions. The findings demonstrate that rainwater harvesting can substantially reduce groundwater consumption while supporting sustainable urban water management. The proposed storage capacity also offers practical guidance for implementing rainwater harvesting systems in institutional buildings with similar climatic and operational characteristics.